The Role of International Sports Organizations in Climate Change and Adaptation - Saleh, Husam Malik (STKIP Taman Siswa Bima, 2025)
This study aimed to identify the roles of international sports organizations in climate change, whether contributing to its increase, limiting, or reducing it, by studying the carbon footprint created by sports facilities, competitions, and activities. It also sought to explore the plans and methods used by these international sports organizations to address the negative effects of climate change. The research problem was represented by the following question: Do international sports organizations have a role in climate change? Whether through adapting to it or contributing to its reduction and mitigation? The researcher assumed that international sports organizations play pivotal roles in influential actions that contribute to reducing climate change in the environment and adapting to it systematically, on the one hand, and, on the other hand, contribute to increasing gas emissions that contribute to increasing the carbon footprint. The timeframe was set from 2017 to 2024, as this is the period during which carbon emissions increased and sports organizations became more effective in partnering with other global organizations to confront the adverse climate changes facing the environment. Spatial boundaries: represented by the largest international organizations influential in climate change: FIFA, the International Olympic Committee, the International Swimming Federation, and the International Association of Athletics Federations. Several scientific approaches were used: descriptive analytical approaches, qualitative and quantitative analysis approaches. The researcher concluded that global sports contribute to an increase in the carbon footprint and environmental pollution, and may be at a greater level than certain countries, especially major tournaments, in addition to the supply chains associated with these events. He recommends encouraging initiatives, educating fans, athletes, and media institutions, and using social media to clarify the link between the sports sector and climate change, and exploiting the influence and fame of athletes to change public behavior towards environmental conservation through climate action.